2003
DOI: 10.1002/dc.10270
|View full text |Cite
|
Sign up to set email alerts
|

Meningioma with extensive noncalcifying collagenous whorls and glial fibrillary acidic protein expression: New variant of meningioma diagnosed by smear preparation

Abstract: The purpose of this report is to describe the unique cytological findings of a new recently characterized type of meningioma that has extensive noncalcifying collagenous whorls and glial fibrillary acid protein (GFAP) expression. This new entity, described by Haberler and colleagues, was named whorling sclerosing variant of meningioma. The patient was a 34-yr-old white man with a large tumor in the brainstem. Intraoperative smear preparations showed a tumor with a large number of solid hyaline masses in a loos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…A few reports have shown that a characteristic feature of sclerosing meningioma is brain invasion5716). However, in our series, only 4 (19%) of 21 cases involved brain invasion.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…A few reports have shown that a characteristic feature of sclerosing meningioma is brain invasion5716). However, in our series, only 4 (19%) of 21 cases involved brain invasion.…”
Section: Discussioncontrasting
confidence: 69%
“…Stevens et al18) reported that the hard consistency of a meningioma is related to the high attenuation observed in CT scans. The very dense collagenous meningioma-like sclerosing type tends to exhibit high attenuation in CT scans1616). All 16 patients in our series with a preoperative CT scan exhibited high attenuation in their tumors.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Recognition of this variant is important for avoiding unnecessary additional postoperative therapy although it is not included into World Health Organization (WHO) classification of CNS tumours. All of the previous reports, however, focused mainly on radiological and clinical features, and there have been few pathologic observations [2,4,5]. Here, we describe five additional cases of sclerosing meningioma, with particular reference to their histologic and immunohistochemical characteristics.…”
Section: Introductionmentioning
confidence: 91%
“…Sclerosing meningioma was first described in 1989 as a histologic variant with a small population of the elongated cells in the collagen‐rich matrix [1]. Seventeen cases of sclerosing meningiomas have been described in the literature [1–5]. Massive tumour sclerosis and frequent brain invasion are prone to being misinterpreted as malignant meningioma or other tumours of the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%